From The Bonn To The Berlin Republic : Germany at the Twentieth Anniversary of Unification. - Anderson, Jeffrey (Berghahn Books, 2010)
The fall of the Berlin Wall and the unification of East and West Germany in 1989/90 were events of world-historical significance. The twentieth anniversary of this juncture represents an excellent opportunity to reflect upon the evolution of the new Berlin Republic. Given the on-going significance of the country for theory and concept-building in many disciplines, an in-depth examination of the case is essential. In this volume, unique in its focus on all aspects of contemporary Germany - culture, historiography, society, politics and the economy - top scholars offer their assessments of th.